Methods for comparing diversification strategies on the Swedish real estate market - Katzler, Sigrid (International Journal of Strategic Property Management, 2016)
This paper compares the effectiveness of different property portfolio diversification strat- egies using five methods; (1) correlation matrices, (2) efficient frontiers, (3) Sharpe ratios, using three different sub methods, (4) coefficients in equations explaining total returns and (5) R-square values in equations explaining total returns. The evaluation methods are applied to both value weighted and equally weighted indices based on Swedish real estate return data. All methods show that, if any, diversifying over property types is a better strategy on the Swedish market than diversifying over re- gions. No test yields significant support for regional diversification. The support for the property type strategy is stronger when using equally weighted indices.